2015
DOI: 10.1124/jpet.115.226936
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Involvement in the Organ Damage and Impaired Spermatogenesis Induced by Testicular Ischemia and Reperfusion in Mice

Abstract: We investigated the role of the nucleotide-binding oligomerization domain (NOD)-like receptor family pyrin domain containing 3 (NLRP3) inflammasome during testis ischemia and reperfusion injury (TI/R) in wild-type (WT) and NLRP3 knock-out (KO) mice. WT and KO mice underwent 1 hour testicular ischemia followed by 4 hours and 1 and 7 days of reperfusion or a sham TI/R. Furthermore, two groups of WT mice were treated at the beginning of reperfusion and up to 7 days with two inflammasome inhibitors, BAY 11-7082 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…Efficacious NLRP3 inflammasome inhibitors are currently at an early stage of research and development. One widely used compound is BAY 11-7082 [ 19 , 20 , 34 , 35 ], an I-κB kinase-β inhibitor, which selectively suppresses the ATPase activity of NLRP3 that is essential for its activation, and directly targets the NLRP3 inflammasome independently of inhibition of NF-κB activation [ 36 , 37 ]. In our studies, this compound inhibited NLRP3 inflammasome activation, reduced spinal cord tissue damage, and improved functional recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacious NLRP3 inflammasome inhibitors are currently at an early stage of research and development. One widely used compound is BAY 11-7082 [ 19 , 20 , 34 , 35 ], an I-κB kinase-β inhibitor, which selectively suppresses the ATPase activity of NLRP3 that is essential for its activation, and directly targets the NLRP3 inflammasome independently of inhibition of NF-κB activation [ 36 , 37 ]. In our studies, this compound inhibited NLRP3 inflammasome activation, reduced spinal cord tissue damage, and improved functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Mice underwent manual bladder expression twice a day until recovery of reflex bladder emptying. The timing and dose of BAY 11-7082 [ 19 , 20 ] and A438079 [ 21 ] were based on previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…As to the role of NLRP3 inflammasome, specific inhibitors, such as BAY 11-7082 [ 100 ] and Brilliant Blue G (BBG) [ 101 ], are able to inhibit its effects in a testicular I/R model [ 102 ]. In fact, BAY 11-7082, an I- κ B kinase- β inhibitor, and BBG, blocking the membrane-bound purinergic P2X7 receptor, showed a significant reduction of IL-1 β and IL-18 mRNA expression, blunted caspase-1 and caspase-3 expression, minor histological damage, low TUNEL activity, and preserved spermatogenesis, indicating a selectively reduced NLRP3 inflammasome activity [ 102 ]. It was also observed that NLRP3 KO mice responded to I/R insult with a lower activation of the inflammatory and apoptosis cascade than WT animals.…”
Section: Ros and Nlrp3 In I/r Injury Of The Testismentioning
confidence: 99%
“…They depend on enzymes (16) and cytokines (17) that participate in inflammatory process of male genitalia (14) . Group of researchers highlighted the importance of inflammasome protein NLRP3 as a "physiological low level of inflammation" for fertility (6).It had been suggested that low level of NLRP3 is essential for Sertoli cell production of low levels of IL1B to maintain IL1 alpha (18) but higher rate of inflammasome expression will results in higher level of inflammasome activation cytokines such as IL-1B and IL-18 (19) and served as a proinflammatory signals generating an inflammatory process in the testis such as leucocyte infiltration and cell death signaling and caspase 1 activation (20)(21)(22) .Also, it might activate ASC adaptor protein in both sperm cell and leucocytes in semen resulting in inflammatory cell death (23) . To date, the primary focus of inflammasome research has been anchored by NLRP3, which is a cytoplasmic protein that is primarily expressed in monocytes, macrophages, granulocytes, dendritic cells, epithelial cells and osteoblasts (24).…”
Section: Discussionmentioning
confidence: 99%